ANALISIS PENGARUH TINGKAT INFLASI, JUMLAH PENGUSAHA KENA PAJAK, NILAI TUKAR RUPIAH DAN SUKU BUNGA SERTIFIKAT BANK INDONESIA TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI DI KOTA SEMARANG PADA TAHUN 2010-2015 - Muhammad Nuhudhul Alim, 13.05.52.0235; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2017)
This research aims to determine the effect of inflation, the amount of taxable entrepreneurs ,exchange rate and interest rate SBI towards Value Added Tax (VAT) revenue either partially or simultaneously. The sample in this study is to cover all of Semarang City during the period 2010 until 2015. The sample used was sixty four and analyzing data for hypothesis testing is done by multiple regression. The results showed that the effect of inflations,the amount of taxable entrepreneurs and interest rate SBIâs effect not significant on Value Added Tax (VAT) revenue, and then exchange rateâs effect significant on Value Added Tax (VAT) revenue. Furthermore, based on adjusted r square can be seen that the effect of inflation, the amount of taxable entrepreneurs ,exchange rate and interest rate SBI can be explained by 88,3%.Keywords: Value Added Tax (VAT) Revenue, The Effect of Inflation, The Amount of Taxable Entrepreneurs, Exchange Rate, Interest Rate SBI